Physical Activity and Diet in Asthma Patients: Benefits, Risks, and Practical Recommendations - A Review of a Literature - Gewald, Maja; Tołkacz, Aleksandra; Sobczak, Julia; Król, Adrianna; Kwiatkowska, Aleksandra; Kosikowska, Aleksandra (Quality in Sport, 2026)
Introduction. Historically, individuals with asthma were often limited in physical activity due to fear of exercise-induced bronchoconstriction, and diet was largely overlooked in routine care. Aim. This narrative review summarizes evidence on benefits/risks of physical activity and diet in asthma management, providing practical recommendations for safe exercise and healthy eating. State of knowledge. Regular physical activity improves cardiorespiratory fitness, exercise tolerance, symptom control, and quality of life in asthma, while reducing inflammation in well-controlled disease. However, exercise can trigger bronchoconstriction, particularly in poorly controlled asthma or with environmental triggers (cold air, allergens, pollution). Dietary patterns significantly influence outcomes: Mediterranean- or plant-rich diets (fruits, vegetables, whole grains, omega-3 foods) improve control and reduce exacerbations, while Western diets (saturated fat, ultra-processed foods) worsen disease severity. Summary. Individualized exercise programs and plant-based dietary patterns should be integrated into asthma management to enhance functional capacity and symptom control. When asthma is well-controlled and environmental factors considered, physical activity and healthy eating are safe and beneficial. High-quality RCTs are needed to optimize protocols and assess long-term impact of combined lifestyle interventions on asthma control.